Y Zeolite-Based Catalyst for Palm Oil Cracking to Produce Gasoline - Algifari, Arif; Makertihartha, I. G. B. N.; Subagjo, Subagjo; Prabowo, Heri (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
The increasing demand for oil fuel and the decline of crude oil reserves highlight the need for alternative energy sources. Palm oil, as a renewable resource, has potential for biofuel production through catalytic cracking. This study aims to develop and evaluate modified zeolite-based catalysts, particularly ZSM-5/HY, to produce palm oil-derived gasoline that meets European fuel standards. The research involved catalyst preparation, modification with ZSM-5 and phosphorus, and activity testing in a fixed-bed reactor. Gasoline yield and catalyst performance were analyzed using gas chromatography. The results showed nearly 100% conversion of palm oil under optimal conditions, with gasoline yield meeting European standard. The addition of ZSM-5 improved conversion and RON, while phosphorus modification reduced catalyst acidity, affecting yield and coke formation. This study concludes that modifying zeolite catalysts with ZSM-5 and phosphorus enables efficient palm oil-derived gasoline production with high RON and reduced aromatic content, contributing to sustainable energy solutions. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).